Dna, Cell Wall and General Oxidative Damage Underlie the Tellurite/Cefotaxime Synergistic Effect in Escherichia Coli - Vasquez-Guzman, C; Muñoz-Villagran, C; Molina-Quiroz, R (2013)
Sin Editorial Disponible